KESEDIAAN REMAJA UNTUK BERPERAN AKTIF DALAM PROGRAM PUSAT INFORMASI DAN KONSELING REMAJA (PIK-R) - Kustia Anggereni; Nurlindawati; Ichsan Trisutrisno (Jurnal Suara Kesehatan, 2023)
Abstract. Based on data from the Central Statistic Agency (2022), the percentage of adolescents ages 20-24 who were married before 18 of age has decreased, from 10.5% in 2020 to 9.23% in 2022 in Indonesia but increased in DKI Jakarta, from 1,45% in 2020 to 4,68% in 2021. The PIK-R program is a program from, by, and for youth which was created to reduce the number of adolescent marriage cases. Hopefully, the risk caused by adolescent marriage can be avoided. So, this study aims to see the willingness of adolescents to play a role actively in this program before and after education about PIK-R is given. This study used a Quasi Experiment method without a control group with One Group Pre-Test and Post-Test approach. The data is primary data collected using a questionnaire instrument which is distributed to the respondent before and after the intervention is given. The analysis of this study uses Paired Samples T-Test. The samples of this study are 100 Students of the 3rd class majoring in office and accounting at Vocational School IP Yakin Jakarta with inclusion and exclusion criteria. The study results are most of the students’ knowledge about PIK-R, their perspective that PIK-R was important, agreement that PIK-R is held in School, and their willingness to participate actively in the PIK-R program are increased after being given education about PIK-R. The conclusion is the willingness of people to accept and apply something new is needed for introduction, learning to be remembered, understood and then applied.